Q-switched and mode-locked erbium-doped fiber laser using gadolinium oxide as saturable absorber - Yusoff, R.A.M.; Jafry, Afiq Arif Aminuddin; Kasim, Nabilah; Zulkipli, Nur Farhanah; Samsamnun, Farina Saffa Mohamad; Yasin, Moh; Harun, Sulaiman Wadi (Elsevier, 2020)
Q-switched and mode-locked Erbium-doped fiber lasers (EDFLs) were demonstrated using gadolinium oxide (Gd2O3) as a saturable absorber. The Gd2O3 nano-powder was embedded into polyvinyl alcohol (PVA) film and integrated into the EDFL cavity to achieve both lasers. At first, a stable Q-switched laser was realized at a center wavelength of 1564.1 nm. The repetition rate increased from 78 to 90.74 kHz and the pulse width reduced from 5.68 to 4.68 µs as the pump power adjusted within 96.28 to 147.16 mW. The output power increased steadily from 19.3 to 26.4 mW as the pump power was raised from 96.28 to 147.16 mW. The slope efficiency of the output power was 14%. Later, a 100 m single mode fiber was incorporated into the similar laser cavity to generate a stable mode-locked laser at a threshold pump power of 96.28 mW with a central wavelength of 1561.5 nm. We observed a stable repetition rate of 1.907 MHz with a pulse width of 3.82 ps as the pump power raised from 96.28 to 147.16 mW. The peak power obtained from the mode-locked laser was tunable from 1.78 to 2.58 kW as the pump power was adjusted from minimum to the maximum. These results indicate the outstanding performance of Gd2O3 SA for both Q-switching and mode-locking applications. The lasers are useful for various applications including, micromachining of material, frequency comb-generation and remote sensing. © 2020 Elsevier Inc.